Human Capital as a Catalyst for Income Convergence: Evidence from ASEAN-8 Countries - Suprayitno, Aziz Wahyu; Gitaharie, Beta Yulianita (Faculty of Economic and Business, 2025)
Research Originality: This study takes a novel approach to analyzing the impact of human capital on income convergence in ASEAN-8 countries by comparing three indicators. This comparative analysis provides a more comprehensive understanding of human capital dynamics in ASEAN's economic convergence.Research Objectives: This study investigates the impact of human capital on income convergence by applying the concept of β-convergence to the ASEAN-8 countries.Research Methods: The analysis of β-convergence is based on the basic and augmented Solow growth models. The estimation is conducted using static and dynamic panel data regression from 1995 to 2019.Empirical Result: The results reveal the existence of absolute and conditional β-convergence in ASEAN-8 countries, suggesting that poor countries grow faster than rich countries, with human capital playing a crucial role in this process. Human capital, measured by average years of schooling, tertiary gross enrolment ratio, and HCI, are important factors that significantly increase income convergence.Implications: ASEAN-8 governments need to establish policies that enhance human capital, particularly in education, by increasing educational attainment and the rate of return to education.JEL Classification: E24, O47, C13How to Cite:Suprayitno, A. W., & Gitaharie, B. Y. (2025). Human capital as a Catalyst for Income Convergence: Evidence from ASEAN-8 Countries. Etikonomi, 24(1), 265 – 284. https://doi.org/10.15408/etk.v24i1.41571.